2008
DOI: 10.1152/ajpregu.00025.2008
|View full text |Cite
|
Sign up to set email alerts
|

Reappraisal of H2S/sulfide concentration in vertebrate blood and its potential significance in ischemic preconditioning and vascular signaling

Abstract: Hydrogen sulfide (H(2)S) is rapidly emerging as a biologically significant signaling molecule. Studies published before 2000 report low or undetectable H(2)S (usually as total sulfide) levels in blood or plasma, whereas recent work has reported sulfide concentrations between 10 and 300 microM, suggesting it acts as a circulating signal. In the first series of experiments, we used a recently developed polarographic sensor to measure the baseline level of endogenous H(2)S gas and turnover of exogenous H(2)S gas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
289
5
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 311 publications
(318 citation statements)
references
References 35 publications
19
289
5
2
Order By: Relevance
“…In rat tissues, O 2 either inhibits H 2 S production or it may be associated with H 2 S consumption and both are reversed by hypoxia (30,44). Similar observations have been made in a variety of tissues from numerous vertebrates (32,89,94,126,128,186). A compelling argument for H 2 S-mediated O 2 sensing can be made by comparing bovine and sea lion lungs.…”
Section: Inverse Relationship Between O 2 and H 2 Ssupporting
confidence: 54%
“…In rat tissues, O 2 either inhibits H 2 S production or it may be associated with H 2 S consumption and both are reversed by hypoxia (30,44). Similar observations have been made in a variety of tissues from numerous vertebrates (32,89,94,126,128,186). A compelling argument for H 2 S-mediated O 2 sensing can be made by comparing bovine and sea lion lungs.…”
Section: Inverse Relationship Between O 2 and H 2 Ssupporting
confidence: 54%
“…H 2 S production by homogenized trout intestine was measured in real time using an amperometric (polarographic) H 2 S sensor constructed in the laboratory (Whitfield et al, 2008). Approximately 1g of anterior intestine was homogenized, on ice, in 9ml of Cortland buffered saline and gassed on a rotary tonometer with humidified 100% nitrogen to remove the oxygen.…”
Section: Effects Of O 2 On H 2 S Productionmentioning
confidence: 99%
“…Although there are many reports of plasma and blood H 2 S concentration between 30 and 300mmoll -1 , these may be experimental artifacts (reviewed in Olson, 2009). In fact, H 2 S may not even exist in the circulation (Whitfield et al, 2008). Recent measurements have also shown that the concentration of H 2 S in a variety of tissues appears to be well below 1mmoll -1 .…”
Section: Are the Effects Of Exogenous H 2 S ʻPhysiologicalʼ?mentioning
confidence: 99%
See 1 more Smart Citation
“…As a result of the technical limitations of available methods 11,12 , H 2 S concentrations spanning 10 5 orders of magnitude have been reported in the literature 13 . Moreover, many of the commonly used methods are not amenable for application in vivo or for analysis of tissue or blood samples.…”
mentioning
confidence: 99%